Four new species of Pseudharpinia Schellenberg, 1931 (Crustacea: Amphipoda: Phoxocephalidae) from southwestern Atlantic and new records of P. tupinamba Senna & Souza-Filho, 2011 - Andrade, Luiz F.; Senna, André R. (Zootaxa, 2020)
Four new species of Pseudharpinia Schellenberg, 1931 are described. The material examined was collected during the Mini Biological Trawl project, off Atlantic’s southwestern coast on the states of Rio de Janeiro, São Paulo, Santa Catarina and Rio Grande do Sul with rectangular dredges at 25 to 500 meters depth. All the new species described present the following remarkable character states that make them easily distinguishable from their congeners: P. bonhami sp. nov. has pereopod 7 basis with 6 large spines posteroventrally; P. jonesyi sp. nov. exhibits pereopod 6 basis with a long acute spiny-projection posteriorly; P. pagei sp. nov. presents head with ventrolateral lines, antenna 1 primary flagellum with stout article 1, gnathopod 2 palm excavate and with slightly serrate palmar hump; P. planti sp. nov. presents head with dorsal keel and ventrolateral line, elongate flagella article 1 of antenna 1, pereopods 3–4 carpus anterior margin with a comb-like structure distally and pereopod 7 merus strongly produced posteroventrally. An identification key for all species of Pseudharpinia of the world is provided.